VIRTUALIZAÇÃO DO ESCRITÓRIO DE GERÊNCIA DE PROJETO: UMA PROPOSTA DE CONVERGÊNCIA DAS DECISÕES ESTRATÉGICAS EM RESULTADOS OPERACIONAIS - Ortega, Eduardo Santana (2009)
This paper consolidates factors influencing virtualization of project management office and through research shows how this new structure can help the spread and implementation of strategic decisions in front of work in environments of multiple projects with geographically dispersed teams that emerged from global competitiveness, the need for low cost, good prospects for growth and spread of the projects of technological advances in information and communication. This paper explores the literature on subjects of strategy and project management, project oriented organizations with the management model, organizational structure and skills to manage projects, virtualization and virtual organizations, functions of the EGP and the advantages and disadvantages of the use of environments virtual. Moreover, this study conducts an analysis and discussion of the results of survey with the participation of 137 professionals working on projects. As a result, it shows the technical factors, behavioral and organizational considered most important in the virtual environment of project management and also the factors that, according to the perspective of virtuality - dispersion, goals, processes and technology, influence these environments virtual. Virtualization in the application of best practices for its structure and use, can be a good way to keep updated with the projects involved the most consistent, real and complete, regardless of geographical location and time. Therefore, this study suggests some functions and virtualization techniques to the project management office, and strengthen certain types of behaviors relevant to this new management style that seeks to contribute and improve the execution / implementation of strategic decisions in environments of multiple projects that companies are focused on development and deployment of your business.